Multimedia Indexing with the SMART system - MARESCA, P.; GUERCIO, A.; ARNDT, T.; TORTORA, G. (Journal of visual languages and computing, 2000)
The storage and retrieval of multimedia data is a crucial problem in multimedia information systems due to the huge storage requirements. It is necessary to provide an efficient methodology for the indexing of multimedia data for rapid retrieval. The aim of this paper is to introduce a methodology to represent, simplify, store, retrieve and reconstruct an image from a repository. An algebraic representation of the spatio-temporal relations present in a document is constructed from an equivalent graph representation and used to index the document. We use this representation to simplify and later reconstruct the complete index. This methodology has been tested by implementation of a prototype system called Simplified Modeling to Access and ReTrieve multimedia information (SMART). Experimental results show that the complexity of an index of a 2D document is O (n*(n−1)/k) with k≥2 as opposed to the O (n*(n−1)/2) known so far. Since k depends on the number of objects in an image more complex documents have lower overall complexity.